Nanomedicine for the Diagnosis and Therapy of COVID-19 - Wang, Yingruo; Hao, Yuanping; Fa, Shunxin; Zheng, Weiping; Yuan, Changqing; Wang, Wanchun (Frontiers in Bioengineering and Biotechnology, 2021)
The coronavirus disease-2019 (COVID-19) pandemics caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been spreading around the world due to its high infection rate, long incubation period, as well as lack of effective diagnosis and therapy or vaccines, which is tearing global health systems apart. It is an urgent demand for point-of-care diagnosis and effective treatment to prevent the spread of COVID-19. Currently, based on the rapid development of functional materials with unique physicochemical features through advanced fabrication and chemical modification, nanomaterials provide an emerging tool to detect SARS-CoV-2, inhibit the interplay in the virus and host cell interface, and enhance host immune response. In our manuscript, we summarized recent advances of nanomaterials for the diagnosis and therapy of COVID-19. The limitation, current challenges, and perspectives for the nano-diagnosis and nano-therapy of COVID-19 are proposed. The review is expected to enable researchers to understand the effect of nanomaterials for the diagnosis and therapy of COVID-19 and may catalyze breakthroughs in this area.